1985
DOI: 10.1111/j.1476-5381.1985.tb10559.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to bradykinin and potassium of the isolated duodenum from rats with genetic and renal hypertension

Abstract: 1 The biphasic (relaxation-contraction) response of the isolated duodenum was used to study the reactivity of non-vascular smooth muscles in genetic (SHR) and renal hypertensive rats compared to their respective controls (WKY and Wistar). 2 For the contractile component of the response to bradykinin, the duodenum from WKY rats was more sensitive, whereas the duodenum from SHR was both more sensitive and hyperreactive, compared to that from Wistar rats. 3 The relaxant component of the response to bradykinin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…We have also noted no difference in the KCl-induced relaxation in TSM pretreated with the calciumchannel blocker, nifedipine (Schramm & Grunstein 1989). Thus, while the potential contribution from other transmitters or ion transport mechanisms cannot be completely ruled out, our findings are comparable to those previously reported using the same method to assay maximal physiological Na+-K+ pump activity in vascular (Feletou & Corticosteroid effects on the airway Na+-K+ pump T et Rinaldi & Bohr, 1989: Shubat et al, 1990, gastrointestinal (Miasiro et al, 1985;Muller et al, 1989), and airway smooth muscle Gunst & Stropp, 1988;Schramm & Grunstein, 1989: Schramm & Grunstein, 1995.…”
Section: Discussionsupporting
confidence: 84%
“…We have also noted no difference in the KCl-induced relaxation in TSM pretreated with the calciumchannel blocker, nifedipine (Schramm & Grunstein 1989). Thus, while the potential contribution from other transmitters or ion transport mechanisms cannot be completely ruled out, our findings are comparable to those previously reported using the same method to assay maximal physiological Na+-K+ pump activity in vascular (Feletou & Corticosteroid effects on the airway Na+-K+ pump T et Rinaldi & Bohr, 1989: Shubat et al, 1990, gastrointestinal (Miasiro et al, 1985;Muller et al, 1989), and airway smooth muscle Gunst & Stropp, 1988;Schramm & Grunstein, 1989: Schramm & Grunstein, 1995.…”
Section: Discussionsupporting
confidence: 84%
“…The relaxation induced by the increase of extracellular potassium is attributed to hyperpolarization due to the stimulation of the Na+/K' pump (Rinaldi et al, 1989). The decreased relaxant response of the SHR and WKY duodenum to potassium confirmed previous findings from our laboratory which showed an inhibition of the Na+/K' pump in this strain (Miasiro et al, 1985). Our results therefore suggest that the normalization of the relaxant response of the SHR by chronic treatment with vitamin D3 may be due to an activation of this pump by vitamin D. The normalization of the Na+/K' pump activity could also contribute to the hypotensive effect of vitamin D3, since Bukosi et al (1986) has already suggested a link between Na+/K' pump activity normalization and the hypotensive effect of dietary calcium.…”
Section: Resultssupporting
confidence: 79%
“…At bradykinin concentrations of 4 nm and above, the SHR duodenum responded with a concentration-dependent contraction preceded by a small relaxation. This predominantly contractile response of the SHR duodenum contrasted with the predominantly relaxant response of the NWR and WKY duodenum, in agreement with a previous report (Miasiro et al, 1985 The SHR which received 2% calcium lactate in the drinking water, or a daily diet supplementation with 12.5 jig vitamin D3, had their blood pressure reduced to normal levels, whereas no significant changes were observed in the blood pressure of WKY animals submitted to the same treatment (Figure 2). …”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations